Temperature Monitoring System using Arduino Uno and Smartphone Application - Arnawan Hasibuan; Kartika; Ahmada Qodri; Muzair Isa (Bulletin of Computer Science and Electrical Engineering, 2021)
This study discusses about temperature monitoring system in the goat pen via smartphone. In addition to monitoring, temperature control is also needed to maintain temperature conditions in the goat pen. This system is useful so that goat cultivation produces well by getting a healthy temperature during its growing period. Manual monitoring is time-consuming, so a more practical monitoring application is required. This monitoring application is built using Internet of Things (IoT) technology so that it can be monitored remotely. The temperature data is taken from the DHT22 temperature sensor which is collected on a microcontroller which is then sent to the internet wirelessly. To control the temperature in the goat pen using an SSR relay. Based on the results of this study, the application of temperature monitoring in the goat pen via smartphone with the Internet of Things (IoT) is able to read the temperature value in the goat pen and can adjust the SSR to turn on and turn off the heating element remotely using a smartphone.